Interactive exemplar-based segmentation toolkit for biomedical image analysis - Xiang Li; Zhi Zhou; Keller, Philipp; Hongkui Zeng; Tianming Liu; Hanchuan Peng (Proceedings (International Symposium on Biomedical Imaging), 2015)
In the field of biomedical imaging analysis on single-cell level, reliable and fast segmentation of the cell nuclei from the background on three-dimensional images is highly needed for the further analysis. In this work we propose an interactive cell segmentation toolkit that first establishes a set of exemplar regions from user input through an easy and intuitive interface in both 2D and 3D in real-time, then extracts the shape and intensity features from those exemplars. Based on a local contrast-constrained region growing scheme, each connected component in the whole image would be filtered by the features from exemplars, forming an "exemplar-matching" group which passed the filtering and would be part of the final segmentation result, and a "non-exemplar-matching" group in which components would be further segmented by the gradient vector field based algorithm. The results of the filtering process are visualized back to the user in near real-time, thus enhancing the experience in exemplar selecting and parameter tuning. The toolkit is distributed as a plugin within the open source Vaa3D system (http://vaa3d.org).